Hypobaric Hypoxia: Effects on Intraocular Pressure and Corneal Thickness. (16th January 2014) - Nebbioso, Marcella; Fazio, Stefano; Di Blasio, Dario; Pescosolido, Nicola
Abstract : Objective . The purpose of this study focused on understanding the mechanisms underlying ocular hydrodynamics and the changes which occur in the eyes of subjects exposed to hypobaric hypoxia (HH) to permit the achievement of more detailed knowledge in glaucomatous disease. Methods . Twenty male subjects, aged 32 ± 5 years, attending the Italian Air Force, were enrolled for this study. The research derived from hypobaric chamber, using helmet and mask supplied to jet pilotes connected to oxygen cylinder and equipped with a preset automatic mixer. Results . The baseline values of intraocular pressure (IOP), recorded at T1, showed a mean of 16 ± 2.23 mmHg, while climbing up to 18, 000 feet the mean value was 13.7 ± 4.17 mmHg, recorded at T2. The last assessment was performed returning to sea level (T4) where the mean IOP value was 12.8 ± 2.57 mmHg, with a significant change (P < 0.05 ) compared to T1. Pachymetry values related to corneal thickness in conditions of hypobarism revealed a statistically significant increase (P < 0.05 ). Conclusions . The data collected in this research seem to confirm the increasing outflow of aqueous humor (AH) in the trabecular meshwork (TM) under conditions of HH.